Čhotmāihēt kānchai sitthi kap sitthibat yā khō̜ng Prathēt Thai (Phǣnngān Phatthanā Sakkayaphāp læ Samatthana dān Kānsāngsœ̄m Sukkhaphāp khō̜ng Thai, Sathāban Wičhai Prachākō̜n læ Sangkhom, Mahāwitthayālai Mahidon, 2008)
Chronicle of the Royal Thai government's making decision to issue a compulsory license on patents covering the AIDS drug efavirenz, to help the AIDS patients in Thailand.